Instabilidade Residencial e Saúde Infantil: Um Estudo de Resultados Múltiplos na Coorte Geração XXI - Ezedei Obinna Benson (2024)
Introduction: Residential instability during childhood can significantly impact health outcomes, yet the complex relationships between mobility, environmental exposures, and child health remain poorly understood. This study investigated the impact of residential moves on diverse health outcomes and examined the effects of changing neighbourhood characteristics in the Generation XXI birth cohort. Methods: We analysed data from 6,397 children followed from birth to age 10. Of these, 38.1% experienced at least one residential move, with 26.1% moving once and 12% moving twice or more. Employing an outcome-wide approach, we assessed the association between instability and 20 health outcomes spanning social-behavioural, cognitive, respiratory, circulatory, anthropometric, and general health domains. Results: Conclusion: